Inception of ecopsychology elements as to strengthen spiritual values among teacher trainees - Muda, Azizi; Kamidin, Tiwi; Roslan, Samsilah; Konting, Mohd Majid; Md Jahi, Jamaluddin; A. Rashid, Noriati (IDOSI Publications, 2011)
This study assessed the impact of incepted ecopsychology elements on spiritual values among teacher trainees. A modified pretest - posttest was used to evaluate the effect of incepted ecopsychology elements in Environmental Education as a quantitative portion. Triangulation with embedded design was used as qualitative portion. Findings showed that there is a significant differences on spiritual values between experimental and control groups. Respondent from experimental groups believed they considered strengthen their spiritual values toward environment after participated in the class even though after four month the treatment activities. Findings from this study suggested the implementation of Environmental Education should incepted ecopsychology elements in order to strengthen spiritual values toward environment.